Case report: Exploring Lynch Syndrome through genomic analysis in a mestizo Ecuadorian patient and his brother - Guevara-Ramírez, Patricia; Ruiz-Pozo, Viviana A.; Cadena-Ullauri, Santiago; Paz-Cruz, Elius; Tamayo-Trujillo, Rafael; Gaviria, Aníbal; Cevallos, Francisco; Zambrano, Ana Karina (Frontiers in Medicine, 2024)
Lynch Syndrome (LS) is a hereditary disorder characterized by genetic mutations in DNA mismatch repair genes, affecting approximately 0.35% of the population. LS primarily increases the risk of colorectal cancer (CRC), as well as various other cancer types like endometrial, breast, and gastric cancers. Microsatellite instability, caused by MMR gene mutations, is a key feature of LS, impacting genes such as MLH1, MSH2, MSH6, and PMS2.Pathology tests studying microsatellite instability and immunohistochemical staining are used to diagnose LS. Furthermore, next-generation sequencing (NGS) allows for a thorough investigation of cancer susceptibility genes. This approach is crucial for identifying affected individuals and managing their care effectively.This study evaluated two siblings who harbored a mutation in the MLH1 gene associated with LS. The older brother was diagnosed with CRC at 24, while the younger brother remains asymptomatic at 7 years old. Genetic testing confirmed the presence of the MLH1 mutation in both siblings. Ancestry analysis showed a mix of African, European, and Native American heritage, common among Ecuadorians. Both siblings shared a family history of cancer, suggesting hereditary factors.Treatment involved surgery and chemotherapy for the older brother, emphasizing the importance of genetic testing for siblings with a cancer family history. NGS plays a pivotal role in identifying genetic mutations and guiding treatment decisions, demonstrating its significance in managing LS and other hereditary cancers.